PENERAPAN STRATEGI PEMBELAJARAN AKTIF LEARNING STARTS WITH A QUESTION (LSQ) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA SMAN 10 PEKANBARU - Irmayani, Sara Fitria; ', Rini; ', Rasmiwetti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this research to increase student achievement on the subject of solubility and solubility product in class XI IPA SMA N 10 Pekanbaru through the implementation of active learning strategy type Learning Starts With A Question (LSQ)). This research was used pretest-posttest design. The sample consisted of two classes, XI IPA 5 class as experiment class and XI IPA 4 class as control class that randomly selected after testing normality and homogeneity. Experiment class was given by implementing active learning strategy type LSQ and the control class was given by discution method. T-test was used to analyse the data. Data of research obtained tcount > ttable (2,503 > 1,67). It means the use of active learning strategy type LSQ could improve student’s achievement on the subject of solubility and solubility product in class XI IPA SMAN 10 Pekanbaru with an increase of 7,81%..Keywords : Active Learning Strategy, Learning Starts With A Question (LSQ), Student’s Achievement, solubility and solubility product